ANALISIS PENGENDALIAN KUALITAS PENYAMAKAN KULIT SAPI NABATI PADA UD ROCHMAH HIDAYAT MENGGUNAKAN METODE PLAN, DO, CHECK, ACT DAN 5W+1H - Tazakka Muhammad Alwi; Andung Jati Nugroho (Jurnal Riset Multidisiplin Edukasi, 2026)
Quality control is a crucial aspect in the leather tanning industry to maintain competitiveness and minimize defective products. UD Rochmah Hidayat faces a problem with defect rates in vegetable-tanned cattle leather production reaching 20% of total production, exceeding the company's quality control limit of 10%. This study aims to identify factors causing defects and formulate improvement proposals to enhance product quality using the Plan, Do, Check, Act (PDCA) method and 5W+1H. Research data was obtained from the production period January to December 2024 with a total of 5,760 leather sheets produced and 1,152 sheets experiencing defects. Analytical tools used include check sheets, Pareto Diagrams, Fishbone Diagrams, control charts, and histograms. Identification results show three dominant types of defects: stiff defects (472 sheets), hole defects (384 sheets), and spot defects (296 sheets). Fishbone Diagram analysis identified main causal factors including human aspects (lack of supervision and accuracy), materials (differences in leather quality from various suppliers and damage due to disease), and methods (errors in the skinning process, imbalance in chemical composition, and improper storage conditions). Control chart analysis shows unstable production processes with several data points outside UCL and LCL limits. Improvement proposals using the 5W+1H method recommend adding supervisors, purchasing raw materials from one trusted supplier, training in knife usage according to standards, standardizing drying time, and using humidity and temperature measuring instruments in warehouses. Implementation of recommendations is expected to reduce defect rates to established control limits.